Reconceptualizing Theft Crimes in Indonesia's 2023 Criminal Code: Living Law and Restorative Justice Critique - Andry Pratama; Sugiyanto Sugiyanto; Wahyu Putra Dwi Pamungkas; Totok Aprianto; Syukron Abdul Kadir (Penerbit Goodwood, 2025)
Purpose: This study aims to examine the reconceptualization of theft crimes under Indonesia's Law Number 1 of 2023 (KUHP 2023) through a legal sociology perspective, analyzing the normative transformation of theft provisions and evaluating their congruence with Indonesian social realities and living law traditions. Research Methodology: This study employs normative legal research (penelitian hukum normatif) integrating statute, conceptual, comparative, and historical approaches. Primary legal materials include KUHP 2023 Articles 362–367, the colonial Wetboek van Strafrecht, and relevant Supreme Court regulations. Theoretical frameworks applied are Eugen Ehrlich's living law theory, Lawrence Friedman's tripartite legal system model, and Roscoe Pound's social engineering theory. Legal materials were systematically collected through Scopus, HeinOnline, Google Scholar, and Indonesia's national legal database (JDIH). Results: KUHP 2023 demonstrates significant normative reconceptualization of theft crimes by integrating retributive, rehabilitative, and restorative justice orientations, formally recognizing living law under Article 2, and incorporating restorative justice mechanisms aligned with Indonesian adat traditions. Conclusions: KUHP 2023 advances post-colonial criminal law reform meaningfully yet incompletely, requiring complementary institutional capacity building and legal culture transformation for full realization. Limitations: This study relies exclusively on normative legal research, excluding direct empirical field investigation of KUHP 2023's implementation realities. Contributions: This study contributes to Indonesian legal sociology scholarship, criminal law reform policy, and judicial practice, providing theoretical and practical insights for legislators, law enforcement authorities, and academics in developing societies navigating post-colonial criminal justice transformation.